Experimental Measurement and Analysis: Collimation and Illumination for Conformity Measuring Instrument Design in X-ray Modality - Fathul Fajar; Andjar Pudji; Achmad Rizal; Muhammad Ridha Makruf (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Each radiology or X-ray device is required to perform a functional or performance test of an X-ray aircraft in accordance with the radiation safety standards of the International Nuclear Energy Agency (IAEA). The suitability test has several parameters and parts. In the X-ray Aircraft Suitability Test, there are X-ray beam collimation tests, X-ray generators and tubes, and AEC. However, the illumination and collimation test still uses the manual method. The purpose of this research is to develop the simplest method, which is to measure the illumination at four points simultaneously and store the measurement data directly. This module is designed to use the HC-SR04 sensor as a distance meter and the TSL2561 sensor as a light meter. This module is designed using the HC-SR04 sensor as a distance meter and TSL2561 sensor as a lux meter. In this research, the module has been tested and compared with the results of a comparison tool (Digital Light Meter) and got an error value of 1.55% with a module efficiency of 98.45% in the illumination test, and an error of 1.8% with a module efficiency of 98.2% in the collimator test. From this research, it can be concluded that the light sensor TSL2561 can be used to measure the illumination area of ​​the collimator lamp. The contribution of this research is expected to be more efficient tool testing, and the data will be saved until the next testing time